2021
DOI: 10.13080/z-a.2021.108.020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of lactic acid bacteria in biocontrol of Aspergillus niger, Penicillium chrysogenum and Fusarium graminearum in culture media and natural substrate

Abstract: Adverse storage conditions impair the quality of stored grain, contribute to the growth and propagation of the fungi leading to an even greater deterioration of the grain quality. Antifungal biopreparations can help preserve grain quality. Lactic acid bacteria (LAB) and their metabolites with antifungal properties can potentially be used in storage conditions or for the decontamination of stored products. The aim of this study was to determine the antifungal activity of Lactobacillus casei, Lactobacillus brevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…However, some LAB species such as L. lactis , Lactococcus and Weissella-oryzae from 7 to 15 days of fermentation and L. brevis and L. dextrinicus from 30 to 60 days of fermentation, were negatively influenced by adding A. niger. The pH level and oxygen amount reduced with the prolongation of silage fermentation, which would significantly influence the propagation and enzyme productions of A. niger ( Dong et al, 2014 ; Kanizai Saric et al, 2021 ), finally altering its influence of silage fermentation as well as the activities of other microbes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some LAB species such as L. lactis , Lactococcus and Weissella-oryzae from 7 to 15 days of fermentation and L. brevis and L. dextrinicus from 30 to 60 days of fermentation, were negatively influenced by adding A. niger. The pH level and oxygen amount reduced with the prolongation of silage fermentation, which would significantly influence the propagation and enzyme productions of A. niger ( Dong et al, 2014 ; Kanizai Saric et al, 2021 ), finally altering its influence of silage fermentation as well as the activities of other microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, L. plantarum MiLAB 393 was reported to produce three antifungal compounds that revealed antifungal effects against various fungi [83]. The fungal strain of A. niger was the most tolerant to treatments with LAB cells and CFSs [84].…”
Section: Bacterial Functionality and Cheese Safetymentioning
confidence: 99%
“…Studies indicated that LAB can produce a variety of antifungal metabolites during the growth process. Many of the antifungal substances of LAB have been proven to have antifungal properties, such as organic acids, ethanol, hydrogen peroxide, bacteriocins, etc., these antifungal and bacterial substances have a synergistic effect, making the cell-free supernatant (CFS) of LAB has a very good inhibitory effect on pathogenic bacteria and fungi ( Kanižai Šaric et al, 2021 ; Wang et al, 2021 ). Currently, liquid chromatography-mass spectrometry (LC-MS) is a powerful and valuable emerging tool for analyzing the metabolites of microorganisms ( Wang and Xie, 2020 ).…”
Section: Introductionmentioning
confidence: 99%